2012
DOI: 10.1128/jcm.02291-12
|View full text |Cite
|
Sign up to set email alerts
|

Association of Relapse of Clostridium difficile Disease with BI/NAP1/027

Abstract: bRecurrent Clostridium difficile infection (CDI) occurs in up to 35% of patients. Recurrences can be due to either relapse with the same strain or reinfection with another strain. In this study, multilocus variable-number tandem-repeat analysis (MLVA) was performed on C. difficile isolates from patients with recurrent CDI to distinguish relapse from reinfection. In addition, univariate and multivariate analyses were performed to identify risk factors associated with relapse. Among patients with a single recurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
108
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(117 citation statements)
references
References 27 publications
6
108
1
2
Order By: Relevance
“…At the time, this change in severity of CDI was attributed to the "hypervirulent" nature of the NAP1/027/B1 strain. NAP1/027/B1 has since become the predominant strain in many locations, and it continues to be associated with high mortality and relapse rates (77). Early studies pointed to heightened toxin expression (78), more efficient sporulation (79,80), expression of the binary toxin, and fluoroquinolone resistance (75) as reasons for the epidemiological success of this strain.…”
Section: Clostridium Difficilementioning
confidence: 99%
“…At the time, this change in severity of CDI was attributed to the "hypervirulent" nature of the NAP1/027/B1 strain. NAP1/027/B1 has since become the predominant strain in many locations, and it continues to be associated with high mortality and relapse rates (77). Early studies pointed to heightened toxin expression (78), more efficient sporulation (79,80), expression of the binary toxin, and fluoroquinolone resistance (75) as reasons for the epidemiological success of this strain.…”
Section: Clostridium Difficilementioning
confidence: 99%
“…This correlates with hospital-specific reports dating back to 2000, where many of the outbreaks were found to have been caused by a NAP1/BI/027 strain and an unexpectedly high mortality rate alerted clinicians to a possible change in CDI epidemiology. In addition, a recent study at the University of Pittsburgh found that patients initially infected by NAP1/BI/027 strains were more likely to relapse than patients infected with other strains of C. difficile (172). Thus, the clinical and surveillance evidence from the past decade shows that an increased frequency of 027 ribotypes correlates with increased mortality.…”
Section: History and Emergence Of Nap1/027/bi Strainsmentioning
confidence: 97%
“…This includes all available full-length sequences from the hypervirulent ribotypes 027 and 078 (n = 15) and all available full-length sequences from the non-hypervirulent ribotype 012 (n = 6). Differences in transmission rates, ability to cause epidemics, toxin production, sporulation and antimicrobial resistance has been documented across C.difficile ribotypes [10,11]; nonetheless, only ribotypes 027 and 078 have been designated as “hypervirulent” based on several factors including increased morbidity and mortality associated with CDI by these ribotypes [1,12,13]. In addition, most studies investigating the mechanisms underlying hypervirulence use ribotype 012 as the reference, representing non-hypervirulent or “typical” strains.…”
mentioning
confidence: 99%